Radio propagation modelling in caves environment - Soo, Qi Ping (2022)
In this thesis, an extensive research on radio wave propagation and modeling in caves environment for cave rescue operation, military surveillance communication networks is undertaken. In this research study, a series of measurement work was conducted in different types of tourist caves and uneven terrains, to investigate the effects of radio wave propagation through cave passages. The path loss in the cave passage for near-ground communication systems, can be empirically modeled using well-known indoor propagation models with the ground reflection taken into application.